East of the Andes: The genetic profile of the Peruvian Amazon populations. Issue 2 (25th March 2017) - Di Corcia, T.; Sanchez Mellado, C.; Davila Francia, T. J.; Ferri, G.; Sarno, S.; Luiselli, D.; Rickards, O.
Abstract: Objectives: Assuming that the differences between the Andes and the Amazon rainforest at environmental and historical levels have influenced the distribution patterns of genes, languages, and cultures, the maternal and paternal genetic reconstruction of the Peruvian Amazon populations was used to test the relationships within and between these two extreme environments. Materials and Methods: We analyzed four Peruvian Amazon communities (Ashaninka, Huambisa, Cashibo, and Shipibo) for both Y chromosome (17 STRs and 8 SNPs) and mtDNA data (control region sequences, two diagnostic sites of the coding region, and one INDEL), and we studied their variability against the rest of South America. Results: We detected a high degree of genetic diversity in the Peruvian Amazon people, both for mtDNA than for Y chromosome, excepting for Cashibo people, who seem to have had no exchanges with their neighbors, in contrast with the others communities. The genetic structure follows the divide between the Andes and the Amazon, but we found a certain degree of gene flow between these two environments, as particularly emerged with the Y chromosome descent cluster's (DCs) analysis. Discussion: The Peruvian Amazon is home to an array of populations with differential rates of genetic exchanges with their neighbors and with the Andean people, depending on their peculiar demographic histories. We highlighted some successful Y chromosome lineages expansions originated in Peru during the pre‐Columbian history which involved both Andeans and Amazon Arawak people, showing that at least a part of the Amazon rainforest did not remain isolated from those exchanges.